2021
DOI: 10.1093/neuonc/noab088
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of genome-wide DNA methylation profiles within the randomized, phase 3, EORTC CATNON trial on non-1p/19q deleted anaplastic glioma

Abstract: Background Survival in patients with IDH1/2 mutant (mt) anaplastic astrocytomas is highly variable. We have used the prospective phase 3 CATNON trial to identify molecular factors related to outcome in IDH1/2mt anaplastic astrocytoma patients. Methods The CATNON trial randomized 751 adult patients with newly diagnosed 1p/19q non-codeleted anaplastic glioma to 59.4 Gy radiotherapy +/- concurrent and/or adjuvant temozolomide. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
5
39
0
Order By: Relevance
“…According to the CBTRUS report, anaplastic astrocytoma (now astrocytoma grade 3) (A3) were more frequent in males, with no significant survival difference between males and females [37]. In line with findings from the CATNON trial, also in the CBTRUS data, the majority of A3 patients were surely IDHmut [16]. We note that the CBTRUS findings for A3 are similar to that of IDHwt GBM, with male dominance, but with small differences in survival between sexes, if any.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…According to the CBTRUS report, anaplastic astrocytoma (now astrocytoma grade 3) (A3) were more frequent in males, with no significant survival difference between males and females [37]. In line with findings from the CATNON trial, also in the CBTRUS data, the majority of A3 patients were surely IDHmut [16]. We note that the CBTRUS findings for A3 are similar to that of IDHwt GBM, with male dominance, but with small differences in survival between sexes, if any.…”
Section: Discussionsupporting
confidence: 52%
“…A change with a larger impact occurred in 2016, when the WHO guidelines for primary brain tumors were updated to include molecular markers [5]. This led to many tumors previously diagnosed as grade 3 glioma being reclassified as IDH wildtype (IDHwt) GBM, for example in the NOA-04 and CATNON studies, where around 30% were found to be IDHwt tumors [15,16]. Approximately 10% of GBMs have been identified as IDH mutated (IDHmut), these previously being secondary GBMs [5], but according to the latest guidelines they are now astrocytoma grade 4 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The unfavorable prognosis of patients with astrocytoma, IDHmt, WHO grade 4 could justify a more aggressive radiotherapy approach with the glioblastoma regimen of 30×2.0Gy. In the CATNON trial, 4-year survival in patients with tumors with a homozygous deletion of CDKN2A/B was around 40% [24]. These survival data support a 33×1.8Gy regime because of the supposed lower risk of long-term toxicity relevant for a considerable percentage of these often young patients [22].…”
Section: Astrocytoma Isocitrate Dehydrogenase Mt Who Grade 4 Based On...mentioning
confidence: 75%
“…Almost all astrocytomas present p53 (94%) alterations, ATRX (86%) loss, or CDKN2A/CDKN2B (cyclin-dependent kinase inhibitor 2A/2B, 10%) homozygous deletion ( 16 , 17 ). Curiously, astrocytomas present often non-canonical IDH1 mutations that are associated with improved survival ( 18 20 ).…”
Section: Idh-mutated Gliomasmentioning
confidence: 99%